Thrombosis and bleeding in cancer patients - Hau C. Kwaan; Brian Vicuna (Frontiers Media S.A., 2011)
It is well recognized that thrombosis and bleeding are two major complications seen in cancer patients. Recent advances in both basic and clinical observations have enhanced our understanding of the pathogenesis of both phenomena. In this article, the significance of thrombotic complications is reviewed first. This is followed by a detailed discussion of the present day concept of thrombogenesis in cancer based on Virchow's original triad of aberrant blood flow, loss of vascular integrity and altered blood components. While most cancer patients experience bleeding at some time during the course of their illness, there are special situations that increase bleeding diathesis. These include thrombocytopenia, endothelial injury, acquired hemophilia and adverse effects of drugs. Recognition of these factors will assit in the adoption of appropriate preventive and therapeutic measures.